2018
DOI: 10.1177/0033354918793096
|View full text |Cite
|
Sign up to set email alerts
|

Using Financial Incentives to Improve Rates of Viral Suppression and Engagement in Care of Patients Receiving HIV Care at 3 Health Clinics in Louisiana: The Health Models Program, 2013-2016

Abstract: Objectives: The Care and Prevention in the United States Demonstration Project aimed to reduce HIV/AIDS-related morbidity and mortality among racial/ethnic minority groups in 8 states. We evaluated Health Models, a pay-for-performance program piloted by the Louisiana Department of Health that used financial incentives to improve rates of engagement in HIV medical care and viral suppression among people with HIV. Methods: We enrolled 2076 patients of 3 urban HIV specialty clinics in Louisiana in the Health Mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…CAPUS provides a model that may be useful for other state and local health departments that aim to address HIV-related racial/ethnic disparities in their jurisdictions. Although our cross-site analysis did not permit us to determine the impact on the incidence of HIV or viral suppression, the short-term outcomes and additional findings reported by grantees 25,26 and observed in other similar projects [27][28][29] suggest that CAPUS could potentially have these desired long-term effects, particularly among racial/ethnic minority groups.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…CAPUS provides a model that may be useful for other state and local health departments that aim to address HIV-related racial/ethnic disparities in their jurisdictions. Although our cross-site analysis did not permit us to determine the impact on the incidence of HIV or viral suppression, the short-term outcomes and additional findings reported by grantees 25,26 and observed in other similar projects [27][28][29] suggest that CAPUS could potentially have these desired long-term effects, particularly among racial/ethnic minority groups.…”
Section: Discussionmentioning
confidence: 86%
“…Although cross-site monitoring and evaluation data on the outcomes of grantees’ initiatives to address HIV-related social and structural factors were not collected, some grantee-specific local evaluations 25,26 suggest that improved availability, accessibility, or acceptability of HIV prevention and care services among racial/ethnic minority groups can be attributed, in part, to efforts to address these factors during the project. CAPUS allowed the delivery of comprehensive services along the HIV care continuum in a manner similar to HIV medical homes, which are designed to address the challenges of fragmented care systems and the complexity and social contexts of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al compared appointment attendance between two groups: one group of patients received phone calls, text messages and mailed letters to remind them about scheduled appointments; another group received a voucher stating the monetary value of their next appointment (although services were provided without cost), watched information videos about the importance of their scheduled appointment, and had their appointments scheduled within a 4‐week period from their initial request date 40 . Two multi‐strategy interventions targeted patients with a history of no‐showing 41,42 . DuMontier et al designed an intervention package that included education about the impact of no‐shows on clinic workflow and patients' health, double‐booking patients who had no‐showed, and same‐day appointment access 41 .…”
Section: Resultsmentioning
confidence: 99%
“…DuMontier et al designed an intervention package that included education about the impact of no‐shows on clinic workflow and patients' health, double‐booking patients who had no‐showed, and same‐day appointment access 41 . Brantley et al financially incentivized appointment attendance and provided patient navigation services that included health education, appointment and treatment adherence counselling 42 …”
Section: Resultsmentioning
confidence: 99%
“…One grantee that implemented an incentive-based strategy shown to be effective for improving engagement and retention in HIV medical care reported that patients used their financial incentives to pay for transportation, housing, and medication costs not covered by insurance (ie, poverty-related barriers to participation in HIV care). 28…”
Section: Address Social and Structural Factors Affecting Testing Nlrmentioning
confidence: 99%